A novel perspective of calvarial development: the cranial morphogenesis and differentiation regulated by dura mater - Li, Danya; Jiang, Xuxi; Xiao, Jing; Liu, Chao (Frontiers in Cell and Developmental Biology, 2024)
There are lasting concerns on calvarial development because cranium not only accommodates the growing brain, but also safeguards it from exogenous strikes. In the past decades, most studies attributed the dynamic expansion and remodeling of cranium to the proliferation of osteoprecursors in cranial primordium, and the proliferation of osteoprogenitors at the osteogenic front of cranial suture mesenchyme. Further investigations identified series genes expressed in suture mesenchymal cells as the markers of the progenitors, precursors and postnatal stem cells in cranium. However, similar to many other organs, it is suggested that the reciprocal interactions among different tissues also play essential roles in calvarial development. Actually, there are increasing evidence indicating that dura mater (DM) is indispensable for the calvarial morphogenesis and osteogenesis by secreting multiple growth factors, cytokines and extracellular matrix (ECM). Thus, in this review, we first briefly introduce the development of cranium, suture and DM, and then, comprehensively summarize the latest studies exploring the involvement of ECM in DM and cranium development. Eventually, we discussed the reciprocal interactions between calvarium and DM in calvarial development. Actually, our review provides a novel perspective for cranium development by integrating previous classical researches with a spotlight on the mutual interplay between the developing DM and cranium.